Complaints and Rectifications During Defect Liability Period: Homebuyer Perspective - Mohd Saufi, .; Liyana, Mohamed Yusof; Rahimi, A. Rahman (Engineering Project and Production Management, 2023)
Due to rapid development and overwhelming demands, housing projects are carried out within a short period. This situation leads to low-quality houses being delivered to homebuyers, which can be seen in the recent trends showing increased numbers of homebuyer complaints about house defects. Thus, this study aims to determine the underlying issues that homebuyers face during the defect liability period (DLP). To achieve that aim, this study investigates the complaints by homebuyers and rectifications by housing developers towards these complaints. Homebuyers who bought directly from developers were interviewed with sets of knowledge questions. The questions include complaints related to the defects that appeared during DLP, the promptness of developers to those complaints, and their rights as a homebuyer towards the complaints. The study findings indicate that the underlying issues during DLP are people, process, and knowledge management. Additionally, although awareness of house defects among homebuyers is increasing, the knowledge of the legal rights during DLP is still low.